Three Years Sustained Complete Remission Achieved in a Primary Refractory ALK-Positive Anaplastic T Large Cell Lymphoma Treated with Crizotinib - Mahuad, Carolina Valeria (Rare Tumors, 2016)
The prognosis of the primary refractory anaplastic lymphoma kinase (ALK+) anaplastic T large cell lymphoma is ominous. The identification of molecular targets with potential to drive oncogenesis remains a cornerstone for the designing of new selective cancer therapies. Crizotinib is a selective ATP-competitive inhibitor for ALK, approved for its use in lung cancer with rearrangements on ALK gene. The reported cases describe the use of crizotinib as a bridging strategy prior to allotransplantation; there are no reported prolonged survivals under monotherapy with Crizotinib. We report a case of a primary refractory ALK+ anaplastic large-cell lymphoma that sustains complete response after 3 years of crizotinib monotherapy.